2021
DOI: 10.37496/rbz5020200189
|View full text |Cite
|
Sign up to set email alerts
|

The 2019 Brazilian survey on nutritional practices provided by feedlot cattle consulting nutritionists

Abstract: Animal production systems and agribusinessFull-length research articleThe 2019 Brazilian survey on nutritional practices provided by feedlot cattle consulting nutritionists ABSTRACT -This survey aimed to provide a current outlook of nutritional recommendations and management practices adopted by feedlot nutritionists in Brazil.The survey questionnaire consisted of 96 questions that included general information on nutritionists, animals, ingredients utilized in finishing diets, management and formulation practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
61
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 24 publications
0
61
0
10
Order By: Relevance
“…Another important type of work is presented in the latest surveys of nutritional recommendations and management practices adopted by feedlot cattle nutritionists [ 43 , 44 ]. The latter studies indicated that diets, such as those used in the finishing feedlots in the current study, are in use in other commercial operations in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Another important type of work is presented in the latest surveys of nutritional recommendations and management practices adopted by feedlot cattle nutritionists [ 43 , 44 ]. The latter studies indicated that diets, such as those used in the finishing feedlots in the current study, are in use in other commercial operations in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Feedlot diets have changed in Brazil, with the increase of concentrate levels in their composition. The usual level of concentrate in Brazilian feedlot diets is between 71% to 90% [ 1 ]. Additionally, the authors reported that 5.56% of Brazilian feedlots used whole shelled corn in their diets.…”
Section: Introductionmentioning
confidence: 99%
“…Among potential feed additives that might be recommended for feedlot cattle, virginiamycin (VM) is a growth promoter that does not decrease the DMI and improves feedlot performance (11), and it was the second feed additive mostly used by Brazilian nutritionists in 2019 (12). When VM was evaluated as an alternative to MON (8), authors reported that Nellore bulls fed VM as the sole feed additive during adaptation reached a DMI of 2% of the initial body weight (BW) in 4.3 days on average, whereas those fed MON needed 20.7 days to reach a similar intake.…”
Section: Introductionmentioning
confidence: 99%